Educação Física e a Precarização do Trabalho Docente: realidade e possibilidades - Sauer, Rosicler Teresinha (2008)
This study is part of the research line New Technologies, Education and Work , of the Master in Education of the Graduate School of the Federal University of Sergipe. It relates to the thematic Physical Education and the precariousness of the teaching: reality and possibilities , aiming at analyzing the teaching conditions in the area of physical education in the municipal schools of Eunápolis-BA from the central points: nexuses with the work in general, its traces and its contradictions. We propose to characterize the changes in the work environment as a result of the trend of destruction of the productive forces and its consequences for the teaching work; to identify the essential traces of the pedagogical work demonstrating its precariousness; to present the contradictions of the teaching work from the organization of the pedagogical work (teaching assignments, goals/evaluation and content/method). The analysis encompasses the professors of Physical Education in the local Department of Culture and Education of the city of Eunápolis-BA. This research has a dialectic materialistic focus, using as instruments the interview and the comment. Also, other analyses of documentation were performed: statute and career plan of the public teachers of the city of Eunápolis, and the school s political pedagogical project. In our research, we noticed that the precariousness of the teaching work in the physical education area, shows the essential traces in the teaching work in the same way as they occur in the general work environment, with the work being overpowered by the capital; as well as we identified that the precariousness of the teaching work in the area of physical education has direct consequences in the pedagogical work. Finally, we evidence the current reality of the teaching work in physical education, as well as we point the possibility of overcoming of the exploitative condition of the education workers, indicating, however, the need for a bigger mobilization, organization, and fight on the part of the workers of themselves.